THE MAQASIDI APPROACH IN ISLAMIC LEGISLATION ACCORDING TO IBN 'ASHUR IN AL-TAHRIR WA AL-TANWIR - Zubairin, Achmad; Muid N, Abd.; Musa, Kamal Fiqry (Peminat Ilmu Ushuluddin, 2024)
This study aims to reveal the crystallization of Islamic law by the Prophet Muhammad SAW who used the maqashidi method which emphasizes the maqashid of Islamic law and the maqashid of the Qur'an. This study uses library research and thematic interpretation methods. This research method uses aspects of library research with data sources of literacy related to manhaj maqashidi and tafsir tahrir wa tanwir as well as works around maqasid sharia and maqasid Al-Qur'an. This study reveals the crystallization of Islamic law by the Prophet Muhammad SAW using the interpretation of Tahrir wa Tanwir, including: 1) protecting religion, 2) protecting the soul, 3) protecting reason, 4) protecting descendants, 5) protecting property. The maqasidi method used by the Prophet Muhammad SAW in crystallizing Islamic law emphasizes the oneness of Allah, the sanctity of man, and human civilization.